Clinical predictors of hypoxemia in patients of acute lower respiratory tract infections: A hospital-based study: Clinical predictors of hypoxemia - Arora, Mansi; Rai, Preeti Lata; Prasad, Prem Lochan (Indian Journal of Child Health, 2022)
Aim: The aim of this study was to study clinical predictors of hypoxemia in patients of acute lower respiratory infections in children.Materials and Methods: An observational prospective study was conducted for 8 months in the General Pediatric Ward and Pediatric Intensive Care Unit of Shri Ram Murti Smarak Institute of Medical Sciences, Bareilly, a tertiary care hospital in Rohilkhand region. This is a hospital-based study. All children admitted with acute lower respiratory tract infections between the age group of 1 month to 59 months of age and diagnosed with pneumonia and bronchiolitis were enrolled and oxygen saturation of patients was recorded and compared with arterial blood gas.Results: A total of 40 patients were enrolled in the study. More than 90% cases of pneumonia and bronchiolitis presented with difficulty in breathing followed by rapid breathing as the next most common symptom. The least common symptom was noisy breathing and pain in abdomen. The most common signs observed were tachypnea which was present in 100% cases of mild, moderate, and severe hypoxemia. Tachypnea (91%), pallor (89%) and nasal flaring (84%), crepitations (added sounds), and subcostal retractions had better sensitivity for detecting hypoxemia.Conclusion: It was observed that a combination of clinical signs and symptoms can be used to predict hypoxemia when facilities of pulse oximetry and arterial blood gas analysis are not available, especially in low-resource settings.